The Impact Of Workload On Job Performance Among Doctors In Malaysian Public Hospitals. A Case Study - Rusli, Ahmad; Lee, Mee Yuen; Abang Ekhsan, Abang Othman; Ahmad Sofian, Shminan; Heng, Chin Siong; Helmi, Sumilan; Abang Ahmad, Abang Izhar (UNIMAS Publisher, 2019)
This research explores the impact of workload on job performance among doctors in a public hospital. A qualitative approach was used, and the method used for data collection is open-ended questionnaires. Purposive sampling was used to collect the data from four informants (doctors) at public hospital, Sarikei, Sarawak. Content analysis was used to analyse the data. Based on the research findings, factors which contribute to the workload among doctors can be categorized into several themes which are insufficient staff, the number of patients, public holidays, disaster events, inadequate equipment, inappropriate working hours and working environment. Findings also show that the short-term impact of workload on doctors’ performance can be positive and negative. For the long-term impact, findings show that doctors’ performance more on the negative aspects relate to the work performance which are tendency to make mistake, intention to leave organization, mental and physical health problem, decrease family relation and increasing divorce rates. This study contributes significantly to the existing body of knowledge on workload and job performance among the doctors from Malaysian public hospitals perspectives and offer a useful view for policy development matters and practitioners as well. This study also discusses related research implication, limitation and recommendation for further research.